R-equol, a synthetic metabolite of the dietary estrogen daidzein, modulates the nongenomic estrogenic effects of 17β-estradiol in pituitary tumor cells. (1st April 2016) - Saraf, Manish Kumar; Jeng, Yow-Jiun; Watson, Cheryl S.
ABSTRACT: We examined nongenomic signaling and functional effects (cell proliferation; prolactin release) of R-equol (R-eq), a synthetically produced metabolite of the phytoestrogen daidzein that preferentially binds to estrogen receptor-α, across a broad concentration range (10 –16 to 10 –7 M). Membrane estrogen receptor-α, via which nongenomic signaling occurs, is enriched in the GH3/B6/F10 pituitary tumor cells used in these studies. We previously reported that other phytoestrogens, including daidzein, are potent inducers of nongenomic signaling acting via membrane receptors for estrogens, resulting in changes to these same functional responses. In the present studies, R-eq activated typical rapid signaling pathways normally evoked by estrogens, but with some differences in response timings and functional outcomes. Levels of R-eq (at 15 nM, a blood level typical for dietary phytoestrogens) were compared to a female physiological level of estradiol (E2 ; 1 nM). Both estrogens activated multiple mitogen-activated protein kinases (ERK, JNK and p38) by phosphorylation within 2.5–15 min, with subsequent oscillations, as observed previously for other estrogens. Like E2, R-eq also augmented intracellular calcium levels and caused prolactin release; in contrast to E2, it did not produce a dose-dependent increase in cell proliferation, as estrogens that activate ERK often do. R-eq and E2, both alone and in combination, activated Gα i by GTP-charging. However, R-eq suppressed 1 nM E2 -activated ERK, JNK and p38, as well as cell proliferation (most pronounced at typical phytoestrogen blood levels of 10 –10 to 10 –7 M). We conclude that R-eq, like E2, is a rapid activator of nongenomic signals, but when combined with E2, can interfere with E2 -induced nongenomic estrogenic effects .